Methods for Assessing Human Embryos to Increase Reproductive Potential (Global Journal of Medical Research, 2022)
The embryological stage of ART programs is one of the most important since the assessment of the quality of oocytes their fertilization and in vitro cultivation to the stage of preimplantation embryos largely determines its success Morphological evaluation of embryos is the main method of embryo selection Time-lapse microscopy is one of the modern methods of selecting a high-quality embryo for transfer In the analysis of many retrospective and prospective studies they emphasize the advantage and lack of differences compared to traditional morphological assessment of the quality of embryos Almost all publications devoted to time-lapse microscopy have focused on determining the timing of specific events of embryo division and then using this information to create algorithms that help to select embryo for transfer
Keywords: assisted reproductive technologies; infertility; elective blastocyst transfer; time-lapse microscopy